THE ETHICS OF BIOTECHNOLOGY IN CUBA: A SOCIO-ANTHROPOLOGICAL PERSPECTIVE ON THE BIOMEDICALIZATION PROCESS - GRABER, Nils (MEDECINE LEGALE DROIT MEDICAL, 2025)
Biotechnology is at the heart of the development project carried out by the Cuban revolutionary government. This process is characterized by a ‘closed-cycle’ organization of R&D. It is mediated by an ethics giving priority to researches that permits to better the health system. This ethics also translates into research practices, which are strongly affected by shortages. Being articulated with the health system, the biotechnology sector is producing transformations that entail specific stakes. By inscribing the Cuban context into a process of biomedicalization, we will discuss stakes related to the management of public health priorities, clinical trials, and the transformation of the experience of illness.